BORDERING, DIFFERENTIAL INCLUSION/EXCLUSION AND CIVIL SOCIETY IN THE UK - Koca, Burcu Toğral (International journal of urban and regional research, 2022)
Taking London as the research context, this article aims to explore the positioning of civil society actors in bordering the differential inclusion/exclusion of asylum seekers and refugees. To do this, and understanding borders/bordering as spaces and social institutions, the article investigates the ways in which civil society actors intervene against bordering, with a particular focus on the labour market and housing. The empirical analysis illustrates that civil society actors seek to open up new spaces of inclusion and new subject positions for refugees and asylum seekers other than those imposed by established bordering processes. However, the capacity of civil society actors to contest the differential inclusion/exclusion enacted in bordering remains limited in the face of constraints produced by neoliberalization and existing political dynamics. More importantly, civil society actors are likely to align themselves with established bordering processes and structures, thus reproducing the differential exclusion/inclusion of asylum seekers and refugees.